Art Athina 2005 : Contemporary Art Fair : Californian artists in Greek Collections. - Henry, Max; Hellenic Art Galleries Association, Athene (Athens : Hellenic Art Galleries Association Athens, 2005)
Baldessari, John ; Durant, Sam ; Halpern, Emilie ; Holloway, Evan ; Isermann, Jim ; Jackson, Richard ; Kelley, Mike ; Kersels, Martin ; Martinez, Daniel Joseph ; McCarthy, Paul ; Meadows, Jason ; Munro, JP ; Pardo, Jorge ; Reed, David ; Shaw, Jim ; Strode, Thaddeus ; Sullivan, Catherine ; Walker, Kara
Publicatie n.a.v. "Art Athina 2005: Contemporary Art Fair" te Athene, 20.05.2005 - 24.05.2005
Engels
Grieks
boek
Keywords: Californië; Griekenland